COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN OBJEK WISATA TOLUK JANGKANG DI KECAMATAN TUALANG KABUPATEN SIAK - Muhammad Aziz Arrasyid; Adianto Adianto (Journal Publicuho, 2021)
Toluk Jangkang Tourism is a tour that has a concept of traveling combining nature with local culture. The concept of Collaborative Governance Helping is important because in its application it does not only involve government and non-government but also other parties. This study aims to examine the concept of Collaborative Governance, the parties involved are the Tourism Office of Siak Regency, PT Cosmic, and Pokdarwis. The collaboration was carried out to develop the Toluk Angkang tourist attraction in Tualang District, Siak Regency. However, there are still inhibiting factors for Collaborative Governance in developing Toluk Jangkang tourism, namely the lack of budget provided by the government and the lack of community participation in developing Antang Jangkang tourism objects. This research method is a descriptive case study approach. The results of the research have not been fully achieved. The collaboration between the Tourism Office of Siak Regency, PT Cosmic, and Pokdarwis has proven that there is still minimal cost and community participation in developing Toluk Jangkang tourism.